Well-being and internal resources during the COVID-19 pandemic in relation to meaning in life and existential anxiety - David, Laura Teodora; Truţa, Camelia (Frontiers in Psychology, 2023)
The COVID-19 pandemic represents an event that placed humanity in a context where confrontation with uncertainty, isolation, life threats and significant changes in one's life were on a scale that exceeded by far previous individual or community crises. The interest of the present research was to investigate the relations between meaning in life (MiL) and existential anxiety (EA) with personal internal resources such as creativity, playfulness, well-being and personal meaning. 451 participants from 48 countries (mean age 34.93 years, standard deviation 12.62, 31.9% male, 67.4% female) were questioned via online questionnaires during May -June 2020. Cluster analysis was performed on meaning of life and existential anxiety that generated four categories of persons: reactive, superficial, preoccupied and dedicated. Well-being and internal resources were associated mostly with dedicated type and less with reactive one. Arguments relying on the existential positive psychology suffering model and the hostile world scenario are presented to support the results and plead for interventions that elicit meaning, stimulate creativity and guide people in finding purpose in order to ultimately promote psychological and mental health.